Ergonomic Analysis in Improving Efficiency and Occupational Health in Shift Work: Literature Review - Permana R, Alief; Hartanto K, Deni; Rahayu A, Dewi; Erlangga P, Muhamad; Prastyo, Yudi (Lentera Ilmu Nusantara, 2024)
This study aims to analyze the application of ergonomic principles in improving occupational efficiency and health in shift work. Through a review of the literature, it was found that ergonomic interventions, such as setting working hours, adding breaks, and designing workplaces accordingly, can significantly reduce fatigue and stress levels in employees. Various studies show that workload adapted to the physical capacity of workers can reduce musculoskeletal complaints and increase productivity. The results of the analysis show that the application of ergonomic principles is not only beneficial for workers' health, but also improves the company's operational efficiency. Therefore, it is recommended that companies consider implementing ergonomic policies in human resource management to create a healthy and productive work environment. This research provides important insights for managers and stakeholders in designing work systems that support employee well-being in a shift work environment.